PERANCANGAN MOTION COMIC 2D PERAN DAN FUNGSI MAMAK DALAM SISTEM KEKERABATAN MINANGKABAU - Affiza Rahmi; heldi heldi (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The contribution and function of information and communication media as information disseminators include studying and preserving the civilization of social and cultural values in the Minangkabau community both in print media, 2D audio visual and 3D media. As today, modern society or the millennial generation does not really care about the role and function of the Mamak towards their nephews, and millennial youth tend to see the values of tracing traditions as ancient, while the influence of outside culture is very vulnerable to be diminished, including in Minangkabau. So there is a need for information and communication media to disseminate education to Minangkabau adolescents such as 2D motion comics which present moving picture stories to discuss the role and function of Mamak in looking after their nephews. As the target audience, Minangkabau youth are expected to be interested in understanding the values of Minangkabau cultural civilization through this motion comic. This design method uses the 4D development model, namely define, design, develop, and disseminate. While the data analysis method uses a SWOT analysis, namely Strengths, Weaknesses, Opportunities, and Threats. The main media in this design work is the Motion comic, which consists of illustrations of moving cutouts where the final result is using Youtube Channel to play Motion comic videos online. Furthermore, it is supported by other media in the form of T-shirts, posters, comics, pins, note books, stickers, x-banners.Keyword: Motion Comic, Mamak, Minangkabau,